THEME AND MORAL VALUES IN “CLOSER THAN VEINS” BY OUTLANDISH - Gumilar Sanjaya; Syahfitri Purnama (INFERENCE: Journal of English Language Teaching, 2020)
Abstract: This research aims to examine the Theme and Moral Values in "Closer Than Veins" by Outlandish. It is a band that originated in Denmark with Hip hop/R&B. The results of this study are to provide insight to readers about the contents of the songs, both themes and moral messages. This research is a qualitative research, where the Theme and Moral Values as independent variable while “Closer Than Veins" as dependent variable. 1). Themes are social problems 38%, moral implication 25%, Coming of age 25%, The complexity of human relationship 12%, The struggle for human dignity 6%, The truth of human nature 0%, A moral or philosophical riddle 0%. 2). Moral values are commitment to something greater than oneself 56%, while the other moral values are self-respect but humanity 25%, self-discipline and acceptance of personal responsibility 19%, respect and caring for others, caring for other living things and environment 0%.Key Words: Theme, Moral values, Song.